Melacak Penyebab Peceraian di Kota Lhokseumawe: Sebuah Penelitian Fenomenologi Hukum Islam - Danial, Danial; Jailani, Munawar Rizki (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
This article examines the causes of divorce in Lhokseumawe, Aceh which is known for its strong Islamic cultural tradition. The research method uses the principles of the phenomenological research paradigm. Primary data was obtained from the results of ethnographic interviews with actors or perpetrators because the focus of this research was directed at tracing the causes and effects of divorce from the perspective of the perpetrators or actors. While secondary data is several kinds of literature related to the research focus. The results showed that several factors cause divorce, namely; differences in character between partners, failure to understand each other, and husband's sexual behavior disorders. The impact of divorce can befall the child and each partner, especially the psychological impact. Similarly, the impact of divorce for couples who already have children with those who do not. For couples who already have children, the impact is wider and inner. Furthermore, efforts to form a divorce can be carried out with several recommendations, First, every couple who will get married must know their potential partner well to their sexual behavior, Second, build a shared commitment about where to go and the desired family model. Third, mutual trust, respect, and support. Fourth, provide good service to partners. Fifth, do not let the small problems that arise in marriage in a long time. Sixth, avoid third-party intervention. Seventh, building a sakinah family requires not only the unity of body and soul but also the same place to live.